PRE-POSITIONING OF A RELIEF CHAIN IN HUMANITARIAN LOGISTICS UNDER UNCERTAINTY IN ROAD ACCIDENTS: A REAL-CASE STUDY - Hosseininezhad, Fatemeh; Makui, Ahmad; Tavakkoli-Moghaddam, Reza (The South African Journal of Industrial Engineering, 2021)
Road accidents, as one of the causes of mortality in human societies, have many adverse social and economic consequences. Various measures can improve the safety of travel. One of them is to find appropriate location of relief infrastructures. The proper pre-positioning of relief chains locations can decrease road users’ fatalities. Thus this paper presents a multi-objective mathematical model to the pre-positioning of a relief chain for road accidents. Then the model is solved by a non-dominated sorting genetic algorithm. Factors that affect the location of relief chains are identified using a multi-attribute decision-making method. Finally, potential locations are proposed for the relief chain locations.